2011
DOI: 10.1029/2011ja016761
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric disturbances triggered by the 11 March 2011M9.0 Tohoku earthquake

Abstract: [1] An earthquake of magnitude 9.0 occurred near the east coast of Honshu (Tohoku area), Japan, producing overwhelming Earth surface motions and inducing devastating tsunamis, which then traveled into the ionosphere and significantly disturbed the electron density within it (hereafter referred to as seismotraveling ionospheric disturbances (STIDs)). The total electron content (TEC) derived from nationwide GPS receiving networks in Japan and Taiwan is employed to monitor STIDs triggered by seismic and tsunami w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
211
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(239 citation statements)
references
References 18 publications
(46 reference statements)
15
211
0
3
Order By: Relevance
“…Artru et al, 2004; Heki and Ping, 2005;Liu et al, 2010). Therefore, the speed of 900 m/s suggests the 2 nd STID being related to AGWs mainly traveling in the ionosphere of about 200 km altitude, which is close to the value of 1032-1045 m/s given by Liu et al (2011) and the 1 km/s (1000 m/s) given by Rolland et al (2011).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Artru et al, 2004; Heki and Ping, 2005;Liu et al, 2010). Therefore, the speed of 900 m/s suggests the 2 nd STID being related to AGWs mainly traveling in the ionosphere of about 200 km altitude, which is close to the value of 1032-1045 m/s given by Liu et al (2011) and the 1 km/s (1000 m/s) given by Rolland et al (2011).…”
Section: Discussionmentioning
confidence: 76%
“…It is essential to find whether this assumption is reasonable and appropriate. Liu et al (2011) report that STIDs of the GPS TEC first appear near the epicenter about 7 minutes after the Tohoku Earthquake onset, while Tsai et al (2011) find that the STIDs in the GPS TEC triggered by the Rayleigh waves appear 7-8 minutes after the earthquake occurrence. Maruyama et al (2011) further cross-compare concurrent/co-located GPS TECs and ionograms recorded by the 4 ionosondes in Japan during the Tohoku Earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…Due to kinetic energy conservation and to the exponential density decrease in the atmosphere, these waves are amplified and generate significant perturbations in the thermosphere/ionosphere system [Peltier and Hines, 1976]. Electron density perturbations due to these gravity waves were observed in GPS data [Artru et al, 2005;Rolland et al, 2010;Galvan et al, , 2012Occhipinti et al, 2013], ionospheric doppler sounders [Liu et al, 2006[Liu et al, , 2011, and ionospheric correction of altimetric satellites [Occhipinti et al, 2006]. Recently, the effect of these gravity waves on the nightside airglow was modeled [Hickey et al, 2010] and observed [Makela et al, 2011], adding a new way to detect tsunami propagation in the thermosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 2011;Tsugawa et al 2011), may provide important opportunities to understand the deformation processes before the occurrence of the mega-thrust earthquakes.…”
Section: Mapping Asperitiesmentioning
confidence: 99%